P-124 The impact of Fragile x premutation carrier state on embryo morphokinetic development, A comparison between genetically normal and abnormal embryos. (30th June 2022) - Shulman, Y; Kalma, Y; Malcov, M; Kopel, R; Azem, F; Almog, B; Cohen, Y
Abstract: Study question: Does inheritance of FMR1 pre mutant allele affect embryos morphokinetic development? Summary answer: Embryos that inherit the FMR1 pre-mutant allele are of a lower morphokinetic quality at the blastocyte stage compared to those with the normal allele. What is known already: Previous studies suggest lower oocyte yield and blastulation rate in FMR1 premutation carriers undergoing preimplantation genetic testing for monogenic diseases (PGT-M). Yet, data is lacking concerning embryo morphokinetic development in this group. Study design, size, duration: Retrospective analysis, on 529 embryos from 126 in vitro fertilization (IVF)- PGT-M cycles of 39 FMR-1 premutation women carriers. Participants/materials, setting, methods: Morphological and morphokinetic parameters acquired by the time-lapse monitoring system were compared between embryos carrying the FMR-1 permutated allele (FMR1 group n = 271) to those who inherited the normal allele (Normal group n = 258). Outcomes measures were embryos morphokinetic parameters up to day 3, the start of blasulation time (tSB) for day 5 embryos, and the rate of top-quality embryos at days 3 and 5. Main results and the role of chance: No differences were found between the groups in all morphokinetic parameters from the time of ICSI until biopsy on day 3. Blastulation rate was comparable between the groups. However, FMR1 embryos exhibited delayed start of blastulation compared to the genetically normal embryos (median tSB 104.2 hrs (99.3-110.3) vs 101.6 hrs (94.5-106.7), P = 0.01) and had lower top quality embryo rate (25.6% vs 38.8%, P = 0.04). Limitations, reasons for caution: This study is limited by its retrospective design and inability to assess CGG expansion in the embryo. Wider implications of the findings: This study offers new insight into the impact of permutated FMR1 gene in the early stages of embryo development. Further studies are needed in order to apply these results in clinical decision-making. Trial registration number: not applicable